Microinvasive Dentistry: A Comparative Study of Resin Infiltration vs. Conventional Methods for Managing Early Caries Lesions in Surabaya, Indonesia - Firman Hadi; Abu Bakar; Mariette Jackson; Aprilia Sari (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Early caries lesions are increasingly prevalent, demanding minimally invasive treatment modalities. This study compared the efficacy of resin infiltration and conventional methods in managing early caries lesions in Surabaya, Indonesia. Methods: A randomized controlled clinical trial was conducted involving 120 patients with early caries lesions. Participants were randomly assigned to three groups: resin infiltration, microabrasion, and fluoride varnish application. Lesion characteristics were assessed at baseline, 6, 12, and 24 months using ICDAS criteria and DIAGNOdent readings. Results: Resin infiltration demonstrated significantly higher success rates in arresting lesion progression compared to microabrasion and fluoride varnish at all follow-up periods (p<0.05). Lesion depth and DIAGNOdent values decreased significantly in all groups, with the most significant reduction observed in the resin infiltration group. Conclusion: Resin infiltration proved to be a superior minimally invasive technique for managing early caries lesions compared to conventional methods. Its ability to effectively arrest lesion progression and improve aesthetics highlights its potential as a valuable treatment option in contemporary clinical practice.